2020
DOI: 10.1096/fj.202000365rr
|View full text |Cite
|
Sign up to set email alerts
|

Gamma ray‐induced glial activation and neuronal loss occur before the delayed onset of brain necrosis

Abstract: Radiotherapy is one of the most effective treatments for head and neck tumors. However, delayed radiation‐induced brain necrosis (RN) remains a serious issue due to the lack of satisfying prevention and effective treatment. The pathological role of radiation in the delayed onset of brain necrosis is still largely unknown, and the traditional animal model of whole brain irradiation, although being widely used, does not produce reliable and localized brain necrosis mimicking clinical features of RN. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 50 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Therefore, targeting radiation-induced neuroinflammation has been considered as a therapeutic strategy to treat RIBI [ 47 ]. Although traditional medicine like corticosteroids and bevacizumab can both alleviate the symptoms of RIBI to a certain extent, their effects on the improvement of neuroinflammation and microglia activation are not significant [ 4 , 8 ]. Notably, our previous study demonstrated that pregabalin could alleviate radiotherapy-related neuropathic pain in the patients with RIBI [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, targeting radiation-induced neuroinflammation has been considered as a therapeutic strategy to treat RIBI [ 47 ]. Although traditional medicine like corticosteroids and bevacizumab can both alleviate the symptoms of RIBI to a certain extent, their effects on the improvement of neuroinflammation and microglia activation are not significant [ 4 , 8 ]. Notably, our previous study demonstrated that pregabalin could alleviate radiotherapy-related neuropathic pain in the patients with RIBI [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic cells were detected by DeadEnd Fluorometric TUNEL System (Promega, G3250) according to the manufacturer’s instructions, as previously described [ 4 ]. Briefly, the slices were permeated in 20 g/ml protease K solution for 20 min and blocked in 5% BSA for 1 h. After washing 3 times with PBS, slices were soaked in equilibrium buffer for 10 min, and then incubated with TDT reaction mixture in the dark at 37 ℃ for 1 h. Finally, DAPI was stained to label the nucleus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Activated microglia causes endocytosis of cell debris and participates in tissue repair in the early stage of cerebral I/R. However, overactivated brain microglia release inflammatory factors, such as TNF- α and IL-6, and participate in chronic inflammation, causing delayed neuronal death, brain edema, and neurological deficits [ 40 , 41 ]. In this study, the results of double immunofluorescence staining showed that the LRP1 was colocalized with microglia, neurons, and astrocytes in the CA1 subregion of the hippocampus at 72 h after cerebral I/R.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying RN involve blood-brain barrier dysfunction, leakage of intravascular inflammatory cytokines, microglia overreaction and subsequent cellular damage 6 , 23 , 24 , 25 ; thus RN on brain MRI typically presents as a contrast-material enhanced white matter lesion with adjacent cerebral parenchymal edema, which if untreated would ultimately lead to cyst formation or even cerebral hernia. 10 , 18 Although some RN could be asymptomatic with mild brain edema at the early stage, the majority of them would progress and eventually become irreversible without effective interventions.…”
Section: Discussionmentioning
confidence: 99%